2013
DOI: 10.1590/s0103-50532013000300015
|View full text |Cite
|
Sign up to set email alerts
|

Applications of molecular modeling in the design of new insect repellents targeting the odorant binding protein of Anopheles gambiae

Abstract: Mosquitos são responsáveis pela transmissão de várias doenças causadas por vírus, parasitas e helmintos. Considerando o custo e a complexidade do tratamento dessas doenças, o uso de repelentes para proteção contra mosquitos vetores se torna uma alternativa interessante. Nesse contexto, no presente trabalho foram feitos estudos por ancoramento e dinâmica molecular (DM) de potenciais ligantes da proteína odorante do mosquito Anopheles gambiae (AgOBP 1 ), o principal vetor da malária. Os modos de ligação na AgOBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Estes compostos já tinham sido observados em outros trabalhos, 1,3,6,16,34,42,43 mas por apresentarem-se como componentes minoritários do produto da extração (valor máximo observado foi de 3,2 %) e segundo Affonso et al (2013) 36 por não demonstrarem interações com a proteína AgamOBP1, sua caracterização e quantificação não foi priorizada. O pico correspondente ao t R 9,7 (min.)…”
Section: Quantificaçãounclassified
“…Estes compostos já tinham sido observados em outros trabalhos, 1,3,6,16,34,42,43 mas por apresentarem-se como componentes minoritários do produto da extração (valor máximo observado foi de 3,2 %) e segundo Affonso et al (2013) 36 por não demonstrarem interações com a proteína AgamOBP1, sua caracterização e quantificação não foi priorizada. O pico correspondente ao t R 9,7 (min.)…”
Section: Quantificaçãounclassified
“…This is more related to the gender than to DEET, as women present lower levels of lactic acid in the blood even after intense physical activity. The lactic acid is one of the constituents of the human sweat and an important attractant to mosquitoes (Affonso, Guimarães, Oliveira, Slana, & França, ). Our results, reported in Figure , therefore, corroborate literature reports.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonds are formed via water molecules with Trp114, Cys95 and Gly92 (Tsitsanou et al , ). Although DEET appears to have a specific interaction with the OBP, it was recently reported that eugenyl acetate could be a better repellent than DEET as a result of a better affinity with the binding site of AgamOBP1, as shown by molecular modelling studies (Affonso et al , ). However, binding assays and robust behavioural bioassays are necessary to corroborate those findings.…”
Section: Methodsmentioning
confidence: 99%